Vegetation und Landschaft in Bayern - Seibert, Paul (ERDKUNDE, 1968)
The 'Map of natural vegetation areas in Bavaria 1 : 500 000 presents the potential natural vegetation of the Land. Because of the scale, only societal complexes, based on dynamic-genetic, topographic and synsystematic criteria and called 'vegetation areas' could be presented. The vegetation map is a deductive or construed map. Soil, geologic, topographic and climatic maps were all used in the delimitation of vegetation units. In addition, a number of excursions were undertaken, in order to test in the field the coincidence between the vegetation areas and the location factors shown on the other maps, and to clear up outstanding questions. The plant-sociologic-systematic division of Oberdorfer (1967) was used as the basis of the division and naming of the vegetation areas. The physiognomically, but also often sociologically-systematically related plant communities or vegetation areas have been aggregated into formation groups in the map key. An ordering of the vegetation geography can be induced from the vegetation map and is presented in Fig. 2: The vegetation regions of Bavaria. Seven vegetation districts are presented in this map, whose differences are determined by the major altitudinal divisions and the broad canvas of climate and can be seen in their varying formation character. The vegetation districts can be further sub-divided into a series of 'growth-type districts' (Wuchsdistrikten). These are conditioned edaphically or through subtler altitudinal differences and are differentiated more in terms of floristic variations within characteristic communities. The individual 'growth-type districts' are briefly described in the section 'The vegetation regions and their plant cover'. The dominant plant communities, giving their name to the whole, and important accompanying communities of the potential natural vegetation are described in structural terms, especially tree type. The recognition of locational individualities, such as soils, bedrock, orography and climatic peculiarities brings vegetation into a relationship with the landscape of each particular growth-type district. These locational individualities, represented through vegetation, form the basis for the varying forestry and agricultural use forms dominant in the growth-type districts, and whose main traits are discussed. 'Vegetation districts' and 'Growth-type districts' as units of vegetation geography define in large measure the total milieu operating on vegetation. They are thus com parable with the 'natural environment units' of the geographer, with which they show some overall agreement.